(untitled) (The International Journal for Scientific Research, 2024)
The aim of this research is to highlight the topic of arbitral proceedings after the removal of the arbitrator in institutional arbitration, a comparative study in the Islamic Shariah and the Saudi regime, since one of the objectives of the Arbitration Act is to study topics relating to arbitration rules and regimes; as a modern system for the adjudication of disputes of all kinds, a system that has begun to spread throughout the world until it comes close to the judicial system as an integral point in the adjudication of disputes. Since the removal of the arbitrator had implications for aspects of arbitration, such as its effect on arbitral proceedings, the present study included two authors: the first examiner examined the consequences of the ruling on the removal of the arbitrator in institutional arbitration, the effects on the powers of the arbitrator after its termination, the extent of the effect of its removal on the award agreement, and the second examiner considered the outcome of the arbitral proceedings after the exclusion of the arbitrator, highlighted the consequences attached to the removal of the arbitrator in accordance with the rules of the Saudi Centre for Arbitration, and clarified the returns to the arbitral proceedings after the arbitrator had been removed from arbitration. The study reached several conclusions, including that the Saudi Centre for Commercial Arbitration rules were compatible with Islamic law and did not oppose the arbitration regime in the removal of the arbitrator, that the arbitral proceedings were related to the arbitrator in existence and non-existence, and that the Arbitration Convention was not affected by the removal of the arbitrator, and that the arbitral proceedings were affected by the removal of the arbitrator in many respects, such as the judgement, and the duration of the case. It is therefore recommended that the competent Saudi judiciary be granted more extensive powers to supervise the arbitral process, where it has adopted the Saudi arbitration system. The study reached several results, including: that the rules of the Saudi Arbitration Center are compatible with Islamic Sharia and do not oppose the system of dismissal of the arbitrator, and that there is no tendency towards slaves of the arbitrator, and it proved that the choice is not affected by the removal of the arbitrator, and the trend is directed towards further from the arbitrator from points a lot; Such as the ruling and the duration of the case. The brief Saudi judiciary is recommended more than the authorities because it allows for supervision of the method heading as it contains the Saudi system.